2021
DOI: 10.1088/2058-6272/abd620
|View full text |Cite
|
Sign up to set email alerts
|

NO x storage and reduction assisted by non-thermal plasma over Co/Pt/Ba/γ-Al2O3 catalyst using CH4 as reductant

Abstract: NO x storage and reduction (NSR) technology has been regarded as one of the most promising strategies for the removal of nitric oxides (NO x ) from lean-burn engines, and the potential of the plasma catalysis method for NO x reduction has been confirmed in the past few decades. This work reports the NSR of nitric oxide (NO) by combining non-thermal plasma (NTP) and Co/Pt/Ba/γ-Al2O3 (Co/PBA) ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The byproducts of N 2 O and N 2 O 5 are not detected in the outlet gas, which indicates that the NH 3 -SCR assisted by NTP does not cause secondary pollution. The following chemical reactions occur in the NTP-SCR system according to the relevant reports [28][29][30]…”
Section: Effect Of Specific Energy Input On No X Conversionmentioning
confidence: 99%
“…The byproducts of N 2 O and N 2 O 5 are not detected in the outlet gas, which indicates that the NH 3 -SCR assisted by NTP does not cause secondary pollution. The following chemical reactions occur in the NTP-SCR system according to the relevant reports [28][29][30]…”
Section: Effect Of Specific Energy Input On No X Conversionmentioning
confidence: 99%
“…Their results showed that the highest NO x reduction efficiency was obtained when CH 4 was added to the reactants. Zhu et al [32], studied the effect of NTP in combination with a Co/PBA catalyst on the NO x removal efficiency under the conditions of NO/CH 4 /O 2 /H 2 O/SO 2 /Ar, and showed that O 2 , H 2 O, and SO 2 had significant effects on NO x reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric barrier discharge (DBD) has been demonstrated as the superior mode for the generation of NTP [19,20]. Nevertheless, NO removal by plasma was mainly attributed to oxidation [21][22][23][24][25], hence ammonia [26,27] and hydrocarbon gas as CH 4 [28,29], C 3 H 6 [30], C 3 H 8 [31], C 7 H 16 [32] and C 8 H 18 [33] are used as reducing gases in many previous studies. However, there is the limitations of gas leakage are yet to be overcome.…”
Section: Introductionmentioning
confidence: 99%